Morphological and molecular characterization of proliferative inflammatory atrophy in canine prostatic samples - Fernandes, Giovana de Godoy [UNESP]; Pedrina, Bruna [UNESP]; Lainetti, Patrícia de Faria [UNESP]; Kobayashi, Priscila Emiko [UNESP]; Govoni, Verônica Mollica [UNESP]; Palmieri, Chiara; de Moura, Veridiana Maria Brianezi Dignani; Laufer-Amorim, Renée [UNESP]; Fonseca-Alves, Carlos Eduardo [UNESP] (MDPI, 2021)
Proliferative inflammatory atrophy (PIA) is an atrophic lesion of the prostate gland that occurs in men and dogs and is associated with a chronic inflammatory infiltrate. In this study, we ret-rospectively reviewed canine prostatic samples from intact dogs, identifying 50 normal prostates, 140 cases of prostatic hyperplasia, 171 cases of PIA, 84 with prostate cancer (PC), 14 with prostatic intraepithelial neoplasia (PIN) and 10 with bacterial prostatitis. PIA samples were then selected and classified according to the human classification. The presence of PIA lesions surrounding neoplastic areas was then evaluated to establish a morphological transition from normal to preneoplastic and neoplastic tissue. In addition, the expression of PTEN, P53, MDM2 and nuclear androgen receptor (AR) were analyzed in 20 normal samples and 20 PIA lesions by immunohistochemistry and qPCR. All PIA lesions showed variable degrees of mononuclear cell infiltration around the glands and simple atrophy was the most common histopathological feature. PIA was identified between normal glands and PC in 51 (61%) out of the 84 PC samples. PIA lesions were diffusely positive for molecular weight cytokeratin (HMWC). Decreased PTEN and AR gene and protein expression was found in PIA compared to normal samples. Overall, our results strongly suggest that PIA is a frequent lesion associated with PC. Additionally, this finding corroborates the hypothesis that in dogs, as is the case in humans, PIA is a pre neoplastic lesion that has the potential to progress into PC, indicating an alternative mechanism of prostate cancer development in dogs.
Keywords: Comparative oncology; Dog; Inflammation; Preneoplastic lesion; Prostatic atrophy